Viral and bacterial coexistence in acute pneumonia in neonatal alpacas - Cirilo C., Erick (2012)
The etiopathogenesis of acute pneumonia, the second most important cause of mortality among Peruvian neonatal alpacas, is still poorly understood. The objective of this study was to characterize gross and histopathology lesions, as well as to identify viruses [parainfluenza type 3 (PI-3) and bovine respiratory syncytial (BRS)] by direct immunofluorescence test, and isolate bacteria [Pasteurella multocida (PM) and Mannheimia haemolytica (MH)] from 24 fatal acute pneumonia cases of 7-39 days-old neonates. At necropsy the gross lesions corresponded to moderate purulent focal bronchopneumonia or severe necrotic purulent fibrinous (n=13), and moderate to severe pulmonary congestion and edema (n=11). Histopathological analysis revealed: acute, severe, and diffuse necrotizing, fibrinous, suppurative bronchopneumonia (n=3), acute mild to moderate and focally diffuse suppurative bronchopneumonia (n=10), and acute, moderate to severe diffuse congestion and pulmonary edema (n=11). Among these 24 cases, 22 yielded virus identification and/or bacterial isolation. Eight cases were positive to one pathogen (5 for viruses and 3 for bacteria), 10/22 were positive for two pathogens [BRSV plus bacteria (n=7), PI-3 plus bacteria (n=2), and one for both bacteria)], and 4/22 positive for 3 pathogens [BRSV, PI-3 plus bacteria (n=3), and PI-3 plus both bacteria (n=1)]. Among the affected lung tissue, virus was identified 19 times (13 positive for BRSV, 9 for PI-3, and 3/19 for both viruses) whereas bacteria was isolated 14 times [P. multocida (n=8), M. haemolytica (n=6), and both bacteria (n=2)]. The presence of multiple pathogens was observed in 14/22 positive cases with an observation of virus-bacteria association in 13/14 of the cases. The coexistence of BRSV-PM was the most frequently observed (6/13), followed by the simultaneous presence of BRSV-MH (4/13) and PI-3 PM or MH (4/13). The results appear to indicate that acute pneumonia in alpaca neonates may well result from virus and bacterial interactions in a similar way to pneumonic lesions of other ruminants.